Za različno vizijo in zaznavo sveta - Zudič Antonič, Nives (Šolsko polje, 2008)
Teachers of Italian as a second or foreign language often tackle the concept of culture when addressing literary topics; cultural issues, however, tend to be dealt with in a superficial, insufficient and predictable way. The importance of culture is indeed emphasised but often only in principle, while an in-depth and gradual approach is neglected. We therefore believe that students, being part of the global community, should be encouraged to develop cultural awareness, which is an important factor in observation and reception of reality in its variety. Several didactic models can be introduced and developed, depending on the level of intercultural awareness; yet a common pattern can be discerned in the learner's response to all of these models, i.e. rejection or disinterest at first, followed by a gradual understanding and acceptance of diversity, and finally, an active involvement with an intercultural environment. The paper draws on a theoretical analysis, supported by suitable practical examples, and aims at showing teachers how they can systematically integrate language knowledge into the cultural context, which is a component of the curriculum.
Keywords: culture; development of intercultural skills; education; intercultural communication; interculturalism; kultura; medkulturna komunikacija; medkulturnost; multiculturalism; razvijanje medkulturne zmožnosti; strategies of language and interculturalism learning; strategije jezikovnega in medkulturnega učenja; Šolsko polje; The School field; vzgoja in izobraževanje